Tuanku Burhanuddin Reviews West Sumatra - Armansyah Armansyah; Abd Mukti; Sapri Sapri (Edumaspul: Jurnal Pendidikan, 2024)
One of the famous reform scholars in West Sumatra is Sheikh Burhanuddin. The purpose of this article is to find out about the life history, scientific spirit and educational system of Tuanku Burhanuddin Ulakan, West Sumatra. The method used in the research is through literature study by carrying out an inventory of all the literature sources used and then carefully verifying them to ensure the level of relevance of the material collected to the object that is the focus of the study in the research. This method is to provide a guarantee of the level of objectivity of the data used. The conclusions from this article are: (1) Sheikh Burhanuddin is thought to have been born in 1056 Hijiriah/1646 AD to a family that adhered to Buddhism. He comes from the Guguk Sikaladi Pariangan area, Padang Panjang, then his parents moved to Sintuak Lubuk Alung. (2) Sheikh Burhanuddin's way of imparting Islamic teachings to the children of Tanjung Medan was in a gradual, soft way. He didn't want to do it hard. The way to do this is to apply one of the verses of the Koran which reads: "Lā Iqraha Fiddīn" (there is no compulsion in religion). (3) It is important to understand that through the Syattariyah congregation which is Sheikh Burhanuddin's means of preaching Islam, Islamic teachings seem to be more easily accepted by the Minangkabau people. Because he presented the Islam of the tarekat which prioritizes the importance of spiritual qualities and inner purification compared to the practices and rituals of the tarekat in general